Classifying stillbirths in a tertiary care hospital of India: International Classification of Disease-perinatal Mortality (ICD-PM) versus cause of death-associated condition (CODAC) system. (17th February 2021) - Sharma, Bharti; Siwatch, Sujata; Kakkar, Nandita; Suri, Vanita; Raina, Ankit; Aggarwal, Neelam
Abstract: A number of classification system are available to classify stillbirths, but there remains a lack of a uniform global system of classification. This study evaluated the feasibility of the ICD-PM classification system and COD-AC to classify the stillbirths and to discuss the interpretation of "the newer" classification system (ICD-PM) over the COD-AC system. Over a period of one year, out of 5776 total births 314 were stillborns with a stillbirth rate of 54 per 1000 total births. As per ICD PM Classification System, 69.1% of stillbirths were ante partum and rest intrapartum. The associated maternal conditions at the time of foetal death were also classified into five groups and maximum mothers (44.3%) were grouped under M4-medical/surgical disorders. According to COD-AC system of classification 90% of cases were assigned the cause of death, rest 10% remained unexplained. The ICD-PM and CODAC classification both seem to be feasible but ICD-PM clearly defines the time of foetal death and correlates feto-maternal dyad together. IMPACT STATEMENT: What is already known on this subject? Classifying stillbirths is crucial to recognise the actual cause of foetal death and to gather the relevant information for planning the preventive strategies especially in low middle-income countries (LMICs) which contribute to 98% of total global burden of 2.6 million stillbirths annually. In literature CODAC system was found most suitable for low middle-income countries. In 2016, WHO proposed a newer system, i.e., ICD-PM: WHO application of ICD-10 to deaths during the perinatal period. What do the results of this study add? With ICD-PM classification stillbirths were categorised more clearly in different groups and feto-maternal condition were linked together along with both intrapartum and ante partum stillbirth which can help to set the priorities and future planning for prevention. The proportion of unexplained stillbirth has also reduced significantly compared to CODAC system. What are the implications of these findings for clinical practice and/or further research? CD-PM system of classification seems feasible and would facilitate the uniform and consistent stillbirth data even from LMICs for global comparison although more number of studies are needed for conclusion. The system has been changed to ICD-PM in our institute.